OPTIMIZATION OF AIRPORT PERSONNEL INSPECTION AT THE MAIN GATE FOR AIRSIDE SECURITY AT HANG NADIM AIRPORT BATAM - Putri Rahmawati, Nazwa; Sukomardojo, Tekat; Arya Soeadyfa Fridyatama, Dimas (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2025)
Airsides are critical areas within airports that require strict access control, particularly for personnel and vehicles entering through the Main Gate. This study aims to assess the current performance of Aviation Security (AVSEC) personnel in conducting screening procedures at the Main Gate of Hang Nadim International Airport and to formulate strategies to optimize these procedures to enhance airside security. The research addresses two main problems: how AVSEC personnel currently perform screening at the Main Gate, and what efforts can be taken to improve and optimize these screening practices. The research uses a qualitative descriptive method with data collection techniques including observation, interviews, documentation, and expert validation. The results show that the screening process is not yet optimal. AVSEC personnel were observed using mobile phones while on duty, inspections of goods were mostly visual due to the unavailability of X-ray and WTMD equipment, and there is no integrated digital recording system nor strict limitations regarding who may access the airside area. These issues create potential security vulnerabilities that could be exploited by unauthorized parties. Therefore, it is necessary to enhance inspection facilities, and implement routine evaluations of personnel discipline to ensure more effective airside security at Hang Nadim International Airport.